Guidance towards conservation decisions: a literature review of historical research documentation aspects / Nur Aina Iylia Husa, Siti Norlizaiha Harun and Mohd Nurfaisal Baharuddin - Husa, Nur Aina Iylia; Harun, Siti Norlizaiha; Baharuddin, Mohd Nurfaisal (Universiti Teknologi MARA, Perak, 2024)
The core concepts of conservation in Malaysia are rooted in the principles of conservation and documentation. These principles lead to the beginning of conservation efforts through the conduction of historical research in the preliminary study, which resulting an initial study report. Historical research is essential to acknowledge the authenticity and significance values of a heritage building as according to Article 6 of the Burra Charter, "the cultural significance of a place and other issues affecting its future are best understood by a sequence of collecting and analysing information before making decisions.". Performing a background study of the place and its extent, as well as looking into its history, usage, associations, and materials can help to comprehend its significant values, which will eventually assist in determining what kind of conservation approach should be undertaken. The objective of the study is to identify historical research aspects that exert an influence on judgements regarding conservation through support by a study of the literature on principles of conservation and documentation, historical research and building characters, which anticipates resulting in historical research aspects that will be documented for the pre-conservation phase.